The sentimental mode : essays in literature, film and television - Williamson, Jennifer A., 1978-; Larson, Jennifer, 1977 July 4-; Reed, Ashley, 1975- (McFarland & Company, Inc., Publishers, 2014)
"Features essays that examine how authors of the 20th and 21st centuries continue the use of sentimental forms and tropes of 19th century literature. While these later narratives employ aspects of the sentimental mode, many critique failures of the sentimental, deconstructing 19th century perspectives on race, class and gender and the ways they are promoted by sentimental ideals"--